Fused mica article and method of making same
Patent Information
- Application Number
- CN202611318369.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-09
AI Technical Summary
对于熔铸云母制品,决定材料强度的是晶界间的结合力,晶粒越粗,晶界结合力越弱,裂纹扩展所需的临界应力越低,晶粒越细,裂纹扩展中遇到的晶界障碍越多,断裂强度越高,然而,现有的熔铸云母制品中晶粒仍然较粗大
本发明的熔铸云母制品及其制备方法,通过加入氧化钇,抑制依赖于层间滑移的晶粒的异常长大,提高熔铸云母的强度性能;同时加入了氧化镧,促使氧化钇的阻止层片滑移与合并的作用效果提高;通过加入钛酸钾晶须,依据裂纹桥接、晶须拔出及裂纹偏转等多重物理增韧机制,大幅提升熔铸云母制品的断裂韧性,并且在凝固过程中为熔体提供骨架支撑,减少因体积收缩导致的集中缩孔,提高熔铸云母制品的致密度。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fused mica technology, specifically relating to a fused mica product and its preparation method. Background Technology
[0002] Fused cast mica, also known as dense fused cast mica, is a synthetic mica microcrystalline aggregate material produced through a high-temperature melting and casting process. It is based on fluorophlogopite (KMg3(AlSi3O4)2) 10 With F2 as its main crystalline phase, it combines the excellent insulation properties of mica with the heat resistance of ceramics, while overcoming the hardness and brittleness defects of ordinary ceramics. It can be machined like metal using turning, milling, planing, and grinding. During the forming process, it is less prone to shrinkage and deformation, and can precisely maintain the product's dimensions and shape. Fused mica possesses excellent properties such as high temperature resistance, oxidation resistance, corrosion resistance, creep resistance, and high resistivity. Therefore, it is widely used in extreme working conditions such as ion nitriding furnace insulation components, submerged arc furnace insulation materials, electromagnetic pump trenches for non-ferrous metal smelting, microwave devices, and particle accelerator ionization chambers—fields requiring high temperatures, high pressures, and strong corrosion.
[0003] Currently, the conventional raw materials for preparing fused cast mica mainly include base materials, fluxes, and nucleating agents. Base materials typically include quartz sand, magnesia, alumina, and potassium carbonate. These components react at high temperatures to form fluorophlogopite crystals. Fluorescent agents reduce melt viscosity and melting temperature. Nucleating agents provide heterogeneous nuclei, promoting overall crystallization and inhibiting excessive grain growth. For fused cast mica products, the strength of the material is determined by the intergranular bonding force. The coarser the grains, the weaker the grain boundary bonding force, and the lower the critical stress required for crack propagation. Conversely, the finer the grains, the more grain boundary barriers encountered during crack propagation, resulting in higher fracture strength. However, existing fused cast mica products still exhibit relatively large grains. The crystallization process of fused cast mica mainly occurs during the annealing stage. During annealing and solidification, the melt undergoes volume shrinkage, easily creating pores within the product and reducing its density. Both large grain size and low density reduce the mechanical strength of fused cast mica products. Summary of the Invention
[0004] The technical problem solved by this invention is to provide a fused cast mica product and its preparation method. By adding yttrium oxide and lanthanum oxide, abnormal grain growth is inhibited and the strength properties of fused cast mica are improved. By adding potassium titanate whiskers, the fracture toughness of the fused cast mica product is significantly improved based on multiple physical toughening mechanisms such as crack bridging, whisker pull-out and crack deflection. Furthermore, during the solidification process, it provides skeletal support for the melt, reduces concentrated shrinkage cavities caused by volume shrinkage, and improves the density of the fused cast mica product.
[0005] To address the aforementioned problems, a first aspect of the present invention provides a cast mica product, the raw materials for which comprise the following components in parts by mass: The ingredients are: 35-50 parts quartz sand, 20-30 parts magnesia, 10-15 parts alumina, 1-5 parts potassium carbonate, 10-20 parts potassium fluorosilicate, 5-20 parts flux, 2-15 parts nucleating agent, 1-3 parts yttrium oxide, 0.3-2 parts lanthanum oxide, and 3-10 parts potassium titanate whiskers.
[0006] Preferably, the raw materials for its preparation include the following components in parts by mass: The composition includes 40-45 parts of quartz sand, 23-27 parts of magnesia, 12-14 parts of alumina, 2-4 parts of potassium carbonate, 13-17 parts of potassium fluorosilicate, 10-15 parts of flux, 5-8 parts of nucleating agent, 1.5-2.5 parts of yttrium oxide, 0.5-1.5 parts of lanthanum oxide, and 5-8 parts of potassium titanate whiskers.
[0007] Preferably, the flux is one or a combination of boron oxide, zinc oxide, and bismuth oxide.
[0008] Preferably, the nucleating agent is one or a combination of several of chromium oxide, titanium oxide, and calcium oxide.
[0009] Preferably, the mass ratio of yttrium oxide to lanthanum oxide is 1 to 5:1.
[0010] Preferably, the particle size of yttrium oxide is 1~5 μm; The particle size of lanthanum oxide is 1~5μm; Potassium titanate whiskers have a diameter of 0.5~2μm and a length of 10~50μm.
[0011] Preferably, the particle size of the quartz sand is 40-100 mesh; the mass content of SiO2 in the quartz sand is >97%; The particle size of magnesia is 16-30 mesh; the mass content of MgO in magnesia is >97%; The particle size of alumina is 120 mesh to 200 mesh; The particle size of potassium carbonate is 16 mesh to 40 mesh; The particle size of potassium fluorosilicate is 120 mesh to 200 mesh.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned cast mica product, comprising the following steps: S1. Mix the raw materials to obtain a mixture; S2. Heat the mixture to 1400~1450℃ and maintain it for 2~3 hours to melt the mixture and obtain a melt; S3. The melt is poured into a mold preheated to 800~900℃ to obtain a casting; S4. Anneal the casting to obtain the fused mica product.
[0013] Preferably, the annealing process specifically involves: first cooling to 530~570℃ and holding for 8~12h; then heating to 580~600℃ at a rate of 10~15℃ / h and holding for 4~6h; then heating to 600~620℃ and holding for 4~6h; and finally cooling to 25~45℃ at a rate of 20~30℃ / h.
[0014] Preferably, when mixing the raw materials, dry ball milling or V-type mixer is used.
[0015] Compared with the prior art, the present invention has the following advantages: The fused cast mica product and its preparation method of the present invention improve the strength properties of fused cast mica by adding yttrium oxide to inhibit abnormal grain growth dependent on interlayer slip; at the same time, lanthanum oxide is added to enhance the effect of yttrium oxide in preventing lamellar slip and merging; by adding potassium titanate whiskers, the fracture toughness of the fused cast mica product is significantly improved based on multiple physical toughening mechanisms such as crack bridging, whisker pull-out and crack deflection, and the product provides skeletal support for the melt during solidification, reducing concentrated shrinkage cavities caused by volume shrinkage and improving the density of the fused cast mica product. Detailed Implementation
[0016] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] A first aspect of this invention provides a cast mica product, the raw materials for which include the following components in parts by mass: The ingredients are: 35-50 parts quartz sand, 20-30 parts magnesia, 10-15 parts alumina, 1-5 parts potassium carbonate, 10-20 parts potassium fluorosilicate, 5-20 parts flux, 2-15 parts nucleating agent, 1-3 parts yttrium oxide, 0.3-2 parts lanthanum oxide, and 3-10 parts potassium titanate whiskers.
[0018] In the fused cast mica product of this invention, quartz sand, magnesia, alumina, potassium carbonate, and potassium fluorosilicate are used as the base materials for fused cast mica. These components undergo a high-temperature smelting reaction to generate fluorophlogopite crystals (KMg3(AlSi3O4)). 10 Fluorophlogopite (F2) can reduce melt viscosity and melting temperature; nucleating agents can provide heterogeneous crystal nuclei, promote overall crystallization, and inhibit excessive grain growth. Fluorophlogopite is a monoclinic layered silicate mineral. Its crystal structure consists of two layers of silicon-oxygen tetrahedrons sandwiching a layer of magnesium-oxygen octahedrons, forming a sandwich structure unit. Adjacent structural units are separated by interlayer K-type ...+ Ions are bonded by relatively weak ionic bonds. Therefore, fluorophlogopite grains are prone to directional merging and stacking due to the slippage and rearrangement of weak interlayer bonding surfaces, leading to excessive grain growth. This invention incorporates yttrium oxide, whose yttrium... 3+ Ions preferentially segregate at the end faces and interlayer defects of layered structures, directly hindering lamellar slippage and merging, thereby suppressing abnormal grain growth dependent on interlayer slip; simultaneously, Y 3+ Ions can also react with K+ in the interlayer. + Competing sites are formed, altering interlayer bonding forces and interlayer spacing, preventing coarsening of grains in a particular orientation, thereby improving the strength properties of cast mica products. Lanthanum oxide contains La³⁺. + Ionic radius greater than Y³ + Ionic radius, La³ + Potassium titanate whiskers can enter the Y₂O₃ lattice or segregate near grain boundaries, causing local lattice distortion. The stress field generated by this distortion can more effectively pin grain boundaries and dislocations, thereby enhancing the effect of yttrium oxide in preventing lamellar slip and merging. Potassium titanate whiskers, distributed within the fluorophlogopite matrix, can significantly improve the fracture toughness of cast mica products through multiple physical toughening mechanisms, including crack bridging, whisker pull-out, and crack deflection. Furthermore, the addition of potassium titanate whiskers can provide skeletal support to the melt during solidification, reducing concentrated shrinkage cavities caused by volume shrinkage and increasing the density of cast mica products.
[0019] Preferably, the raw materials for its preparation include the following components in parts by mass: The composition includes 40-45 parts of quartz sand, 23-27 parts of magnesia, 12-14 parts of alumina, 2-4 parts of potassium carbonate, 13-17 parts of potassium fluorosilicate, 10-15 parts of flux, 5-8 parts of nucleating agent, 1.5-2.5 parts of yttrium oxide, 0.5-1.5 parts of lanthanum oxide, and 5-8 parts of potassium titanate whiskers.
[0020] Within the above-mentioned mass fraction range, the mechanical properties of the obtained fused cast mica products can be improved.
[0021] Preferably, the flux is one or a combination of boron oxide, zinc oxide, and bismuth oxide.
[0022] Preferably, the nucleating agent is one or a combination of several of chromium oxide, titanium oxide, and calcium oxide.
[0023] Preferably, the mass ratio of yttrium oxide to lanthanum oxide is 1-5:1. The addition of lanthanum oxide can enhance the effect of yttrium oxide in preventing lamellar slip and coalescence. However, excessive addition of lanthanum oxide can lead to excessive segregation of rare earth oxides at grain boundaries, forming coarse second-phase particles, which weakens the effective suppression of interlayer slip. It may also cause localized lattice distortion concentration, microcracks, or excessive rare earth ions entering the interlayer positions, excessively altering the interlayer bonding force and weakening the grain boundaries, resulting in decreased material density, increased brittleness, and ultimately a decrease in mechanical strength. When the above-mentioned mass ratio of yttrium oxide to lanthanum oxide is used, appropriate amounts of both can improve the performance of cast mica products.
[0024] Preferably, the particle size of yttrium oxide is 1~5 μm.
[0025] Preferably, the particle size of lanthanum oxide is 1~5 μm.
[0026] Preferably, the potassium titanate whiskers have a diameter of 0.5~2μm and a length of 10~50μm.
[0027] Preferably, the particle size of the quartz sand is 40-100 mesh; and the mass content of SiO2 in the quartz sand is >97%.
[0028] Preferably, the particle size of the magnesia is 16-30 mesh; and the mass content of MgO in the magnesia is >97%.
[0029] Preferably, the particle size of alumina is 120 mesh to 200 mesh.
[0030] Preferably, the potassium carbonate has a particle size of 16 mesh to 40 mesh.
[0031] Preferably, the particle size of potassium fluorosilicate is 120 mesh to 200 mesh.
[0032] A second aspect of this invention provides a method for preparing the above-mentioned cast mica product, comprising the following steps: S1. Mix the raw materials to obtain a mixture; S2. Heat the mixture to 1400~1450℃ and maintain it for 2~3 hours to melt the mixture and obtain a melt; S3. The melt is poured into a mold preheated to 800~900℃ to obtain a casting; S4. Anneal the casting to obtain the fused mica product.
[0033] Preferably, the annealing process specifically involves: first cooling to 530~570℃ and holding for 8~12h; then heating to 580~600℃ at a rate of 10~15℃ / h and holding for 4~6h; then heating to 600~620℃ and holding for 4~6h; and finally cooling to 25~45℃ at a rate of 20~30℃ / h.
[0034] This application employs a multi-stage annealing process. First, the temperature is lowered to 530-570℃ and held for an extended period, promoting the formation of numerous fine and uniform crystal nuclei within the melt, forming the basis for subsequent fine-grained structures. Then, the temperature is raised to 580-620℃ at an extremely slow rate, allowing crystals to grow steadily and fully on the existing nuclei, preventing abnormal coarsening of some grains due to excessively rapid heating. Finally, the temperature is slowly cooled to room temperature, effectively eliminating thermal stress accumulated during crystallization and preventing cracking of the product due to mica's low thermal conductivity and excessive internal and external temperature differences. It also avoids problems such as disordered crystal orientation and porosity caused by excessively slow cooling. This annealing process helps refine grains, increase material density, and eliminate internal stress, resulting in cast mica products with excellent mechanical strength and structural integrity.
[0035] Preferably, when mixing the raw materials, dry ball milling or V-type mixer is used.
[0036] Example 1 The raw materials for preparing the fused cast mica product in this embodiment include the following components in parts by weight: 42 parts of 60-mesh quartz sand, 25 parts of 20-mesh magnesia, 13 parts of 200-mesh alumina, 3 parts of 20-mesh potassium carbonate, 15 parts of 200-mesh potassium fluorosilicate, 12 parts of 200-mesh zinc oxide, 6 parts of 200-mesh chromium oxide, 2 parts of yttrium oxide with a particle size of 3 μm, 1 part of lanthanum oxide with a particle size of 3 μm, and 6 parts of potassium titanate whiskers with a diameter of 1 μm and a length of 30 μm.
[0037] The method for preparing the cast mica product in this embodiment includes the following steps: 1. Weigh all raw materials precisely according to the above formula, and use dry ball milling to fully mix the raw materials to ensure that each component is evenly dispersed to obtain a mixture.
[0038] 2. Place the mixture into a crucible and heat it in a high-temperature electric furnace to 1400°C. Maintain the homogenization time for 3 hours to completely melt and homogenize the raw materials, thus obtaining a melt.
[0039] 3. Quickly pour the homogenized melt into a mold preheated to 800°C to obtain the casting. The pouring method and speed can be selected according to the shape and size of the casting.
[0040] 4. Place the casting in an annealing furnace for precisely controlled annealing to obtain the fused mica product. The specific steps of the annealing process are as follows: first, cool to 550℃ and hold for 10 hours; then, heat to 580℃ at a rate of 10℃ / hour and hold for 6 hours; then, heat to 600℃ and hold for 6 hours; finally, cool to 40℃ at a rate of 20℃ / hour and slowly cool to room temperature in the furnace before removing the casting.
[0041] Example 2 The raw materials for preparing the fused cast mica product in this embodiment include the following components in parts by weight: 40 parts of 60-mesh quartz sand, 27 parts of 20-mesh magnesia, 12 parts of 200-mesh alumina, 4 parts of 20-mesh potassium carbonate, 13 parts of 200-mesh potassium fluorosilicate, 15 parts of 200-mesh zinc oxide, 5 parts of 200-mesh chromium oxide, 2.5 parts of yttrium oxide with a particle size of 3 μm, 0.5 parts of lanthanum oxide with a particle size of 3 μm, and 8 parts of potassium titanate whiskers with a diameter of 1 μm and a length of 30 μm.
[0042] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0043] Example 3 The raw materials for preparing the fused cast mica product in this embodiment include the following components in parts by weight: 45 parts of 60-mesh quartz sand, 23 parts of 20-mesh magnesia, 14 parts of 200-mesh alumina, 2 parts of 20-mesh potassium carbonate, 17 parts of 200-mesh potassium fluorosilicate, 10 parts of 200-mesh zinc oxide, 8 parts of 200-mesh chromium oxide, 1.5 parts of yttrium oxide with a particle size of 3 μm, 1.5 parts of lanthanum oxide with a particle size of 3 μm, and 5 parts of potassium titanate whiskers with a diameter of 1 μm and a length of 30 μm.
[0044] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0045] Example 4 The raw materials for preparing the fused cast mica product in this embodiment include the following components in parts by weight: 35 parts of 60-mesh quartz sand, 30 parts of 20-mesh magnesia, 10 parts of 200-mesh alumina, 5 parts of 20-mesh potassium carbonate, 10 parts of 200-mesh potassium fluorosilicate, 20 parts of 200-mesh zinc oxide, 2 parts of 200-mesh chromium oxide, 3 parts of yttrium oxide with a particle size of 3 μm, 0.3 parts of lanthanum oxide with a particle size of 3 μm, and 10 parts of potassium titanate whiskers with a diameter of 1 μm and a length of 30 μm.
[0046] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0047] Example 5 The raw materials for preparing the fused cast mica product in this embodiment include the following components in parts by weight: 50 parts of 60-mesh quartz sand, 20 parts of 20-mesh magnesia, 15 parts of 200-mesh alumina, 1 part of 20-mesh potassium carbonate, 20 parts of 200-mesh potassium fluorosilicate, 5 parts of 200-mesh zinc oxide, 15 parts of 200-mesh chromium oxide, 1 part of yttrium oxide with a particle size of 3 μm, 2 parts of lanthanum oxide with a particle size of 3 μm, and 3 parts of potassium titanate whiskers with a diameter of 1 μm and a length of 30 μm.
[0048] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0049] Example 6 In this embodiment of the fused cast mica product, the mass proportions of the remaining components in the raw materials are the same as in Example 1, except that: 1.5 parts of yttrium oxide with a particle size of 3 μm and 1.5 parts of lanthanum oxide with a particle size of 3 μm are used. That is, the total mass proportions of yttrium oxide and lanthanum oxide remain unchanged, and their mass ratio is 1:1.
[0050] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0051] Example 7 In this embodiment of the fused cast mica product, the mass proportions of the remaining components in the raw materials are the same as in Example 1, except that: 2.5 parts of yttrium oxide with a particle size of 3 μm and 0.5 parts of lanthanum oxide with a particle size of 3 μm are used. That is, the total mass proportions of yttrium oxide and lanthanum oxide remain unchanged, and their mass ratio is 5:1.
[0052] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0053] Example 8 In this embodiment, the mass proportions of the remaining components in the raw materials for the fused casting mica product are the same as in Example 1, except that: 1 part of yttrium oxide with a particle size of 3 μm and 2 parts of lanthanum oxide with a particle size of 3 μm are used. That is, the total mass proportions of yttrium oxide and lanthanum oxide remain unchanged, and their mass ratio is 0.5:1.
[0054] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0055] Example 9 In this embodiment of the cast mica product, the mass proportions of the remaining components in the raw materials are the same as in Example 1, except that: 2.8 parts of yttrium oxide with a particle size of 3 μm and 0.2 parts of lanthanum oxide with a particle size of 3 μm are used. That is, the total mass proportions of yttrium oxide and lanthanum oxide remain unchanged, and their mass ratio is 14:1.
[0056] The preparation method of the cast mica product in this embodiment is the same as that in Example 1.
[0057] Comparative Example 1 The cast mica product of this comparative example was prepared using the same mass proportions of the remaining components in the raw materials as in Example 1, except that yttrium oxide was not added. The preparation method of the cast mica product of this comparative example was the same as that of Example 1.
[0058] Comparative Example 2 The cast mica product of this comparative example was prepared using the same mass proportions of the remaining components in the raw materials as in Example 1, except that lanthanum oxide was not added. The preparation method of the cast mica product of this comparative example was the same as that of Example 1.
[0059] Comparative Example 3 The cast mica product of this comparative example was prepared using the same mass proportions of the remaining components in the raw materials as in Example 1, except that potassium titanate whiskers were not added. The preparation method of the cast mica product of this comparative example was the same as that of Example 1.
[0060] Comparative Example 4 The raw materials for the fused cast mica product in this comparative example are the same as those in Example 1. The difference is that the annealing process is as follows: the temperature is lowered to 600°C at a rate of 10°C / h, held for 10 hours, then lowered to 40°C at a rate of 20°C / h, and slowly cooled to room temperature in the furnace before the casting is removed.
[0061] The material density, compressive strength, and flexural strength of the cast mica products of the above embodiments and comparative examples were measured, and the test results are shown in Table 1 below.
[0062] Table 1
[0063] As shown in Table 1, the cast mica of Comparative Example 1, which did not contain yttrium oxide in its raw materials, and the cast mica of Comparative Example 2, which did not contain lanthanum oxide in its raw materials, had low material density and insufficient compressive and flexural strength. The cast mica of Comparative Example 3, which did not contain potassium titanate whiskers, also had low material density and insufficient compressive and flexural strength. In Comparative Example 4, the annealing process did not include a nucleation stage at 530-570℃. Due to the different temperature dependence curves of nucleation and crystallization, the formation of crystal nuclei was slow, while the few formed nuclei grew rapidly, ultimately resulting in a coarse grain structure. Furthermore, the crystallization stage was not divided into two phases for stable crystallization and sufficient grain development, failing to ensure stable and orderly growth of crystal nuclei at a low supersaturation level. This resulted in excessively large grains and poor material strength.
[0064] The fused mica of each embodiment in this application exhibits significantly higher material density and better compressive and flexural strength. Among them, Examples 1-5 differ in the mass fraction of the raw materials used in preparation; Examples 1-3 are preferred embodiments, exhibiting better compressive and flexural strength. Examples 1 and 6-9 differ in the mass ratio of yttrium oxide to lanthanum oxide; Examples 1, 6, and 7 are preferred embodiments, exhibiting better compressive and flexural strength.
[0065] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A cast mica product, characterized in that, Its preparation raw materials include the following components in parts by mass: The ingredients are: 35-50 parts quartz sand, 20-30 parts magnesia, 10-15 parts alumina, 1-5 parts potassium carbonate, 10-20 parts potassium fluorosilicate, 5-20 parts flux, 2-15 parts nucleating agent, 1-3 parts yttrium oxide, 0.3-2 parts lanthanum oxide, and 3-10 parts potassium titanate whiskers.
2. The cast mica product according to claim 1, characterized in that, Its preparation raw materials include the following components in parts by mass: The composition includes 40-45 parts of quartz sand, 23-27 parts of magnesia, 12-14 parts of alumina, 2-4 parts of potassium carbonate, 13-17 parts of potassium fluorosilicate, 10-15 parts of flux, 5-8 parts of nucleating agent, 1.5-2.5 parts of yttrium oxide, 0.5-1.5 parts of lanthanum oxide, and 5-8 parts of potassium titanate whiskers.
3. The cast mica product according to claim 1, characterized in that: The flux is one or a combination of boron oxide, zinc oxide, and bismuth oxide.
4. The cast mica product according to claim 1, characterized in that: The nucleating agent is one or a combination of several of chromium oxide, titanium oxide, and calcium oxide.
5. The cast mica product according to claim 1, characterized in that: The mass ratio of yttrium oxide to lanthanum oxide is 1 to 5:
1.
6. The cast mica product according to claim 1, characterized in that: The particle size of yttrium oxide is 1~5μm; The particle size of lanthanum oxide is 1~5μm; Potassium titanate whiskers have a diameter of 0.5~2μm and a length of 10~50μm.
7. The cast mica product according to claim 1, characterized in that: The particle size of the quartz sand is 40-100 mesh; the mass content of SiO2 in the quartz sand is >97%; The particle size of magnesia is 16-30 mesh; the mass content of MgO in magnesia is >97%; The particle size of alumina is 120 mesh to 200 mesh; The particle size of potassium carbonate is 16 mesh to 40 mesh; The particle size of potassium fluorosilicate is 120 mesh to 200 mesh.
8. A method for preparing a cast mica product as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Mix the raw materials to obtain a mixture; S2. Heat the mixture to 1400~1450℃ and maintain it for 2~3 hours to melt the mixture and obtain a melt; S3. The melt is poured into a mold preheated to 800~900℃ to obtain a casting; S4. Anneal the casting to obtain the fused mica product.
9. The preparation method according to claim 8, characterized in that: The annealing process specifically involves the following steps: first, cooling to 530-570℃ and holding for 8-12 hours; then, increasing the temperature to 580-600℃ at a rate of 10-15℃ / hour and holding for 4-6 hours; then, increasing the temperature to 600-620℃ and holding for 4-6 hours; and finally, cooling to 25-45℃ at a rate of 20-30℃ / hour.
10. The preparation method according to claim 8, characterized in that: When mixing the raw materials, dry ball milling or V-type mixer is used.